PENINGKATAN HASIL PEMBELAJARAN SBdP MATERI DAUR ULANG KERTAS BEKAS MENGGUNAKAN METODE PEMBELAJARAN BERBASIS EKSPERIMEN PADA KELAS V SD NEGERI 007 SAMARINDA ULU TAHUN AJARAN 2024/2025 - Della Julia Sari; Muhlis; Taufik Hidayat; Andi Asrafiani Arafah; Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of fifth grade students ofSDN 007 Samarinda Ulu, especially in the Arts and Culture subject. The purpose ofthis research is to determine the improvement in the learning outcomes of Arts andCulture on the Recycling of Used Paper Material by Using Experiment-BasedLearning Methods for Fifth Grade Students at SDN 007 Samarinda Ulu in the2024/2025 Academic Year.This type of research is Classroom Action Research (CAR) which is conducted intwo cycles and each cycle consists of two meetings. The procedure of this researchconsists of four stages, namely planning, implementation, observation, reflection.The subjects in this study were 21 students of class V A SDN 007 Samarinda Uluand the object of this research was the results of learning Arts and Culture usingexperimental-based learning methods. Data collection techniques in this study usedobservation, tests and documentation. The instruments in this study used teacheractivity observation sheets, student activity observation sheets and student learningoutcome test sheets. The data analysis techniques in this study used averagevalues, percentages and diagrams.The results of the study showed an increase in the average value of students fromthe pre-cycle value of students 54.57 with a percentage of completion of 39%. Student learning outcomes in cycle I experienced an increase of 15% from the pre-cycle baseline value, with an average class value of 64.76 with a percentage of completion of 52%. Cycle II learning outcomes experienced an increase of 39.17%from the pre-cycle baseline value, with an average value of 75.95 with a percentageof completion of 85.71% with 18 students completing and 3 students not completing,and achieving more than the expected success indicator of 75%. Based on theresults of the study, it can be concluded that there was an increase in the learningoutcomes of Arts and Culture on the material of Recycling Used Paper UsingExperiment-Based Learning Methods in Class V A Students of SDN 007 SamarindaUlu in the 2024/2025 Academic Year.